Factors Affecting Students’ Pursuance to Complete the Bachelor of Science in Accountancy Course - Ayore, Rufelle Mae M.; Fornoles, Merelle Rose F.; Layto, Vivienne Rozenn G.; Miralles, Marie Antoinette C.; Diokno, Chester Owen B.; Lopez, Glenda Joy B.; Lintao, Evely G.; Abas, Reynaldo P.; Borromeo, Robert A. (8ISC Abstract Proceedings, 2022)
The accounting profession has always played a vital role in the business world because of the financial information that helps in the decision-making of businesses. Statistics from several studies indicate a downward trend in accounting graduates. Therefore, this study determined the factors affecting the students’ pursuance to complete the Bachelor of Science in Accountancy (BSA) program, given that several studies indicated a decline in the enrolment of accounting degrees. The factors considered were stereotypes, social conditions, social status, and economic reasons. The correlational method of research was employed to gather information using survey questionnaires. The study was conducted in three selected higher education institutions in the Philippines with a total of 145 freshmen and sophomore students, chosen through stratified sampling. Regression analysis revealed that stereotypes and economic reasons significantly influence the students’ degree of pursuance to BSA courses. The findings implied that students who are less likely to stereotype and have stronger economic reasons are more likely to complete the accountancy program. On the contrary of the results, the factors social conditions and social status do not significantly influence the pursuance of the students. The study also revealed that regardless of year level and sex, students’ degree of pursuance remains unaffected. One implication of this study is for students to disregard the stereotypes of the accounting profession and focus more on the economic reasons to have a higher level of pursuance to finish the accountancy course. They must understand the scope of the profession to be more dedicated to becoming an accounting professional Keywords : pursuance to complete the Bachelor of Science in Accountancy (BSA) stereotypes, social conditions, social status, and economic reasons